The Effect of Electronic Service Quality on Increasing Customer Loyalty with a Focus on Adding Diverse Product Segments - Dafa Rafif Pratama; Angga Febrian; Driya Wiryawan; Nurul Husna (Universitas Hayam Wuruk Perbanas, 2023)
Using e-commerce platforms to improve product marketing is the right choice for every business in the digital era. According to recent research, online shopping is increasingly popular among customers who prefer to shop without physically visiting a store. This study aims to investigate the quality of electronic services provided by online e-commerce stores to encourage customer satisfaction and loyalty. This study measures the quality of electronic services in terms of website design, customer service, security/privacy, and fulfillment using the most recent WebQual model. The Partial Least Square method (SmartPLS-v3) was utilized to analyze the sample data collected using 159 respondents who met the specified criteria as the research sample. The research demonstrates that all hypotheses are found to have significant positive results. Positive correlations have been found between the four dimensions of the model and the quality of electronic services, as well as their impact on customer satisfaction and intentions to stay loyal. This study is beneficial for determining the electronic service model customers in online e-commerce stores want to gain customer loyalty.